Real‐world characteristics and treatment of cardiac transthyretin amyloidosis: A multicentre, observational study - Richard J. Nies; Svenja Ney; Ingrid Kindermann; Yvonne Bewarder; Angela Zimmer; Fabian Knebel; Katrin Hahn; Sebastian Spethmann; Peter Luedike; Lars Michel; Tienush Rassaf; Maria Papathanasiou; et al. (ESC Heart Failure)
Abstract Aims Data on the clinical profiles of patients with transthyretin amyloidosis cardiomyopathy (ATTR‐CM) in the post‐approval era of tafamidis 61 mg are lacking. Study aims were characterization of contemporary ATTR‐CM patients, analysis of potential eligibility for the ‘Transthyretin Amyloidosis Cardiomyopathy Clinical Trial’ (ATTR‐ACT) and identification of factors associated with the decision on tafamidis 61 mg treatment. Methods and results This retrospective study analysed ATTR‐CM patients seen at eight University Hospitals in the first year after approval of tafamidis 61 mg for ATTR‐CM in Germany (April 2020 to March 2021). The cohort comprised 366 patients (median age 79 [74; 82] years, 84% male), with 47% and 45% of the cohort being in National Amyloidosis Centre ATTR stage ≥ II and NYHA class ≥ III, respectively. Sixty‐four per cent of patients met key eligibility criteria of the pivotal ATTR‐ACT. In recently diagnosed patients (58% with diagnosis ≤6 months), the rate of variant ATTR was significantly lower than in patients diagnosed more than 6 months ago (9.3% vs. 19.7%). Of the 293 patients without prior ATTR specific treatment, tafamidis 61 mg was newly initiated in 77%. Patients with tafamidis 61 mg treatment were significantly younger, were more often eligible for ATTR‐ACT, had lower NYHA class and higher serum albumin levels. These variables explained 16% of the variance of treatment decision. Unadjusted survival was higher in patients with than those without treatment (1‐year survival 98.6% vs. 87.3%, P < 0.001). Conclusions Wild‐type ATTR was the primary aetiology amongst contemporary ATTR‐CM patients and almost two‐thirds of patients were in an advanced disease stage. Clinical profiles of 64% of patients in routine care matched those of the ATTR‐ACT. Further effort is needed to detect patients at an earlier disease stage and to validate criteria justifying treatment initiation.